Intraosseous myofibroma of mandible: A rarity of jaws: With clinical, radiological, histopathological and immunohistochemical features - Sundaravel, Subbaraj (Medknow Publications & Media Pvt Ltd, 2013)
Myofibroma is an uncommon benign mesenchymal neoplasm composed of myofibroblasts, but it can be confused with more aggressive spindle cell tumors. Solitary myofibroma is common in soft tissues of head and neck, but rare in the jaw bones with only 38 cases of central myofibroma of mandible reported in English medical literature. When encountered in the jaws, lesions exhibit clinical and radiographic features suggestive of odontogenic cysts/tumors or other neoplastic conditions. We hereby present the 39(th) case of intraosseous myofibroma of the mandible which had been reported to our institution. A 16-year-old male reported with a chief complaint of swelling in the right side of face. Intraorally there was a firm, nontender swelling in the right buccal aspect of the mandible. Radiologically the lesion was osteolytic, destroying the buccal cortical plate. Histologically, characteristic biphasic pattern of myofibroma was noticed. Immunoreactivity was positive for vimentin and αSMA but negative for desmin, thus confirming our diagnosis. The patient was treated by local-wide surgical excision of the lesion. A 3-year follow-up revealed no signs of recurrence. Occurrence of myofibroma involving the jaw bones is common in the younger age groups and represents a unique diagnostic and therapeutic challenge. Differentiating this lesion from other benign and malignant neoplasms is crucial in deciding between a radical and a conservative treatment approach.